ANALISIS PENERAPAN PENGEMBANGAN KEMAMPUAN KERJA TERHADAP PRESTASI KERJA DI PT. PELABUHAN INDONESIA IV MAKASSAR (PERSERO) - Nurwahidah Mashuddin (Movere Journal, 2022)
The purpose of this study was to determine the effect of work ability on employee performance at PT Pelabuhan Indonesia IV Makassar (Persero) either partially or simultaneously. This research is an explanatory research using a quantitative approach and data collection techniques through questionnaires and observations. The sample used as many as 75 respondents in the company. The data analysis used is descriptive analysis and multiple linear regression analysis. Meanwhile, to test the hypothesis, the F-Test and T-Test are used. The results of hypothesis testing show that; 1) Simultaneously, work ability has a positive and significant effect on the work performance of PT Pelabuhan Indonesia IV Makassar (Persero). 2) The variable of work ability that has a dominant effect on work performance at PT Pelabuhan Indonesia IV Makassar (Persero).